If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+7=3(x+9)
We move all terms to the left:
4x+7-(3(x+9))=0
We calculate terms in parentheses: -(3(x+9)), so:We get rid of parentheses
3(x+9)
We multiply parentheses
3x+27
Back to the equation:
-(3x+27)
4x-3x-27+7=0
We add all the numbers together, and all the variables
x-20=0
We move all terms containing x to the left, all other terms to the right
x=20
| 8x6x=8x+4x+12 | | 5x-3=2.5x+14.5 | | -2x+5x-15=3(x-3)-24 | | X-13=x+2 | | 7.5x-8=2.5x+12 | | 0.04x+0.17(x+9000)=2790 | | 2x+11=9x-17 | | x/3+8=48 | | (1/5)(-2x+4)(1/3)=x-1 | | 3x-9=11x-25 | | 4x-4/3=32 | | -6x+6-7(x-1)=-(5x-3)-7x+7 | | 6x+10=x-25 | | 4x+9x=41 | | 18x=86 | | 6(u-4)=8 | | 3/5x-18=33 | | 2(30x+20)=420 | | 63+3y=10y | | 3x+10=9+7x+1 | | 4x-9=2(2x+5) | | 6(x-2)=9(x+2) | | 2+b/3=-3 | | -3(4–x)=5–(x+1) | | 3x-3(4-3x)=4(x-3)-40 | | -12u-9+7=26 | | 2w+38=14w-94 | | 8y-40=-16 | | 17a-42=2a+63 | | 2y+66=3y+18 | | .50x=x-13 | | -6b-4b=-6(2b-5)-2(11b-9) |